Avaliação da remoção de norfloxacino em solução aquosa utilizando a ozonização - Danusa Campos Teixeira (2014)
Antibiotics are substances that have been frequently detected in natural water. Studies show low removal of these substances by conventional methods of water and wastewater. The actual effects of drinking water contaminated by these substances are not known yet. Due to the low removal submitted by conventional processes, advanced oxidation processes become good alternative to the persistent degradation of these molecules. The ozonation is one of the most applied techniques for the removal of drugs from aqueous matrices. This study aimed to evaluate the process of removal and mineralization of norfloxacin, an antibiotic frequently detected in natural water. The removal process chosen for the study was the development of ozonation at pH = 3 and 11. The trials lasted 60 min and the flow of ozone of 2 and 4 mL / min ozone were adopted. The results showed that the removal of norfloxacin was above 99 % for all flow conditions of pH and ozone adopted. Despite the proximity of the median removals found for the two groups of pH studied, statistical tests show that there are statistical differences with significance of 5 % between the groups. The mineralization in alkaline medium (indirect mechanism) reached approximately 90 % removal of total organic carbon to the doses of ozone. Already in acid medium (direct mechanism) to remove approximately 45% for the two flows studied. As expected, the pH groups studied also showed statistical difference for the removal of total organic carbon. The acute toxicity test showed that the solution of crude norfloxacin is toxic. The toxicity increases when the solution is treated in acid pH and decreases when the treatment is carried out at alkaline pH. The mass balance for the ozonation system was made. The calculations showed that much of the injected ozone passed through the reactor as unchanged and was retained in the off - gas. The mass transfer constant for the reactor was measured for pH and analyzed with a flow of 4 mL/min of ozone. The kinetic tuning of the reaction between ozone and norfloxacin was determined and the condition that best fit the data was the pseudo-first order. The ozonation is a good alternative for the removal of aqueous samples norfloxacin, particularly at alkaline pH, because a high mineralization was attained and reduced toxicity of the antibiotic.